Suicide terrorism and the weakest link - Arce, Daniel G.; Kovenock, Daniel J. 1956-; Roberson, Brian (CESifo, 2009)
In this paper we examine a model of terrorism which focuses on the tradeoffs facing a terrorist organization that has the ability to utilize either or both suicide and conventional terrorism tactics. The terrorist organization’s objective is to successfully attack at least one target. Success for the target government is defined as defending all targets from any and all attacks. In this context, we examine how terrorist entities strategically utilize suicide attacks when other modes of attack are available, and the optimal anti-terrorism measures. -- conflict ; suicide terrorism ; weakest link ; Colonel Blotto
Keywords: Selbstmordattentat; Abwehr; Terrorismus